Using erlang in research and education in a technical university - Petrov, Iurii; Alexeyenko, Andrey; Ivanova, Galina (Wydawnictwa AGH, 2018)
This paper addresses the problem of using functional programming (FP) languages for research and educational purposes. In order to identify the problems associated with the use of FP languages such as Erlang, an experiment consisting of two surveys was performed. The first survey was anonymous and aimed at establishing whether the participants prefer object-oriented or functional coding. The second one was a survey made after the students finished an Erlang course. The results of these two surveys demonstrate that functional programming is underrated with no apparent reasons. Possible steps to address this problem are suggested.
Computer Science
Bibliogr. s. 342-343.
Keywords: parallel programming; distributed programming; teaching; graph theory; concurrency; recursion; survey; functional programming